2022
DOI: 10.1097/mcg.0000000000001695
|View full text |Cite
|
Sign up to set email alerts
|

An Evidence-based Practical Guide to Vaccination for Hepatitis B Virus

Abstract: The hepatitis B virus (HBV) is highly infectious, with over 292 million chronically infected people worldwide and up to 2.4 million in the United States. Following infection, clinically silent liver damage can ensue, but symptoms or signs of advanced disease, including cirrhosis and hepatocellular carcinoma, can take decades to emerge. HBV has the heaviest public health burden of all hepatitis viruses and has now surpassed other major communicable diseases (eg, HIV, diarrheal disease, malaria, tuberculosis) as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 105 publications
0
1
0
Order By: Relevance
“…7 Measures including intradermal (ID) route, use of third generation vaccines with newer adjuvants or immunostimulants have reported better response rates. 8 Administration of ID HBV in healthy children 9 and in those with conditions like celiac disease 10 has shown comparable seroprotection rates of more than 90% similar to that of the primary Hep B vaccination. While, multiple studies in adults 11 have shown better efficacy of ID HBV route in non-responders to the IM route; no study to the best of our knowledge has been conducted in pediatric hemodialysis patients.…”
Section: Introductionmentioning
confidence: 99%
“…7 Measures including intradermal (ID) route, use of third generation vaccines with newer adjuvants or immunostimulants have reported better response rates. 8 Administration of ID HBV in healthy children 9 and in those with conditions like celiac disease 10 has shown comparable seroprotection rates of more than 90% similar to that of the primary Hep B vaccination. While, multiple studies in adults 11 have shown better efficacy of ID HBV route in non-responders to the IM route; no study to the best of our knowledge has been conducted in pediatric hemodialysis patients.…”
Section: Introductionmentioning
confidence: 99%